Viral Cell Entry Induced by Cross-Linked Decay-Accelerating Factor - Shafren, Darren R. (American Society for Microbiology, 1998)
Decay-accelerating factor (DAF) mediates cellular attachment for many human picornaviruses. In most cases, viral binding to DAF is itself insufficient to permit cell infectivity, with a second, functional internalization receptor being required to facilitate this process. Previously, we postulated that the role of DAF in enterovirus cell infection is as a sequestration receptor, maintaining a reservoir of bound virus in an infectious state, awaiting interaction with functional internalization receptors. Many of these functional receptors possess the capacity to induce relatively rapid changes in capsid conformations, resulting in the formation of altered particles (A-type particles). In this report, we show that antibody-cross-linked DAF, in contrast to endogenous surface-expressed forms, can act as a functional virus receptor to mediate coxsackie A21 virus (CAV21) lytic cell infection. In contrast to the situation with ICAM-1-mediated CAV21 infection, in which high levels of A-type particles are formed, cross-linked DAF-induced CAV21 replication occurs in the absence of detectable A-particle formation.